2015
DOI: 10.3389/fpsyg.2015.00270
|View full text |Cite
|
Sign up to set email alerts
|

Does long-term object priming depend on the explicit detection of object identity at encoding?

Abstract: It is currently unclear whether objects have to be explicitly identified at encoding for reliable behavioral long-term object priming to occur. We conducted two experiments that investigated long-term object and non-object priming using a selective-attention encoding manipulation that reduces explicit object identification. In Experiment 1, participants either counted dots flashed within an object picture (shallow encoding) or engaged in an animacy task (deep encoding) at study, whereas, at test, they performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…This should have effectively and considerably reduced differences in cognitive effort between contrasting T A B L E 1 Results from the multilevel logistic regression model predicting category membership (FA, CR) from pupillary response and BOLAR index predictors (Model 1), and the multilevel regression model predicting pupil dilation from BOLAR index and response category (Model 2) categories. Although we acknowledge that RT-matching may still be insufficient to perfectly match effort and familiarity strength between any two categories, changes in RTs remain a popular proxy for cognitive effort (Beatty, 1982;Gomes & Mayes, 2015a, 2015bMontefinese et al, 2013;Porter et al, 2007;Võ et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…This should have effectively and considerably reduced differences in cognitive effort between contrasting T A B L E 1 Results from the multilevel logistic regression model predicting category membership (FA, CR) from pupillary response and BOLAR index predictors (Model 1), and the multilevel regression model predicting pupil dilation from BOLAR index and response category (Model 2) categories. Although we acknowledge that RT-matching may still be insufficient to perfectly match effort and familiarity strength between any two categories, changes in RTs remain a popular proxy for cognitive effort (Beatty, 1982;Gomes & Mayes, 2015a, 2015bMontefinese et al, 2013;Porter et al, 2007;Võ et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…However, in terms of the priming task, as long as participants were consistent in how they named the item, even if they could not identify it visually, then the name they used was irrelevant. Recent research has demonstrated that long-term object priming does not depend on explicit detection of object identity during the encoding stage 35 . Importantly, all participants demonstrated significant implicit memory via repetition priming: i.e., repeated items in this context are more predictable, leading to a reduced reaction time, compared with novel items.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the relational memory theory proposes that the hippocampus is involved in the processing and representation of relational information regardless of whether retrieval is made with or without conscious awareness. Long‐term repetition priming is a kind of stimulus‐specific memory for studied items, arguably independent of conscious awareness (e.g., Gomes and Mayes, ; Gomes et al, ), in which one or more exposures to a stimulus facilitate or bias performance in memory tasks that do not make reference to these previous encounters (e.g., Schacter, ; Richardson‐Klavehn and Bjork, ). Whereas single item priming is thought to involve mainly occipitofrontal structures (see Buckner and Koutstaal, ; Henson, for reviews) as well as the perirhinal cortex (PRC; e.g., Wang et al, ; Dew and Cabeza, ), there is an emerging body of evidence linking the hippocampus to the encoding and retrieval of associative unaware memories, where behavioral facilitation is shown when previously encountered pairs of unrelated items are repeated (see Hannula and Greene, for a review; but see Verfaelllie et al, ).…”
Section: Introductionmentioning
confidence: 99%